2010
DOI: 10.3390/ma3094639
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Al-Al3Ti/Ti3Al Functionally Graded Materials under a Centrifugal Force

Abstract: Fabrication of Al-Al3Ti functionally graded materials (FGMs) under the centrifugal force has recently attracted some attention. The controlled compositional gradient of the fabricated FGMs, the low cost of the process, and the good mold filling, are the main advantages of the centrifugal method (CM). Using the conventional CM techniques such as the centrifugal solid-particle method and centrifugal in-situ method, FGMs rings with gradually distributed properties could be achieved. As a more practical choice, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…This phenomenon has been explained through the precedent study for Zhang et al [13], where they owed the decreased volume fraction of the Al 3 Ti particles to the severe fragmentation of the Al 3 Ti particles by ECAP, followed by the supersaturation of Ti into the Al matrix. This phenomenon of supersaturation was also confirmed for Al/Al 3 Zr FGMs as a result of severe wear tests conditions, described elsewhere [20]. Considering these reported results, further decrease of the Al 3 Zr volume fraction in the current samples is expected if larger strains were applied.…”
Section: Mechanical Tests Of Ecaped Al/al 3 Zr Samplessupporting
confidence: 83%
“…This phenomenon has been explained through the precedent study for Zhang et al [13], where they owed the decreased volume fraction of the Al 3 Ti particles to the severe fragmentation of the Al 3 Ti particles by ECAP, followed by the supersaturation of Ti into the Al matrix. This phenomenon of supersaturation was also confirmed for Al/Al 3 Zr FGMs as a result of severe wear tests conditions, described elsewhere [20]. Considering these reported results, further decrease of the Al 3 Zr volume fraction in the current samples is expected if larger strains were applied.…”
Section: Mechanical Tests Of Ecaped Al/al 3 Zr Samplessupporting
confidence: 83%
“…Considering the fact that the most remarkable characteristic is that super-gravity can significantly promote the relative motion between solid-liquid, gas-liquid and liquid-liquid because of the difference in density. [27][28][29][30][31][32][33] What's more, our previous study 24) reported that the "crystal rain" caused by super-gravity was contributed to the mechanism of the grain refinement of Al-Cu alloys. Therefore, it is expected that a similar mechanism is occurring in super-gravity field as a result of the moving behavior of crystal nuclei.…”
Section: Figmentioning
confidence: 97%
“…Observation of the manufactured specimen indicated an increasing trend in the hardness profile from the outer surface to the TiC-rich inner surface. The wear performance of the TiC-rich inner face was found to be better when compared to the particle free outer surface of ferritic steel matrices [46].…”
Section: Infiltration Processmentioning
confidence: 91%